Universal Cash Transfers and Labor Market Outcomes. (1st December 2022) - Bibler, Andrew; Guettabi, Mouhcine; Reimer, Matthew N.
Abstract: One major criticism of Universal Basic Income is that unconditional cash transfers discourage recipients from working. Evidence to date has largely relied on targeted and/or conditional transfer programs. However, it is difficult to draw conclusions from such programs because universal transfers may induce a positive demand shock by distributing cash to a large portion of the population, which may in turn offset any negative labor supply responses. We estimate the causal effects of universal cash transfers on short‐run labor market activity by exploiting the timing and variation in size of a long‐running unconditional and universal transfer: Alaska's Permanent Fund Dividend. We find evidence of both a positive labor demand and negative labor supply response to the transfers. Small negative effects on the number of hours worked are found for women, especially those with young children. In contrast, we find an increase in the probability of employment for males in the months following the distribution. Altogether, a 1, 000 increase in the per‐person disbursement leads to a 0.8 percent labor market contraction on an annual basis.